The Effect of New and Traditional Sources of Financing on the Performance of Small and Entrepreneurship Businesses: The Case of Qatar - Mohammed M. Elgammal (17316970) (2023)
Purpose This paper investigates how entrepreneurial finance in Qatar affects the performance of small and entrepreneurship businesses (SEB). It is the first study examining the financial decisions of SEB in Qatar, illustrating the advantages and disadvantages of traditional and innovative sources of finance. In addition, we investigate the impact of different funding sources on three dimensions of SEB performance: financial, marketing and internal business and development performance. Methodology Our sample included 300 SEB owners and managers, selected randomly and contacted in January to March 2020. Following the delivery and collection process, the study obtained 161 questionnaires, which were analysed using ordinary least squares regression. Findings The results suggest that diversity and accessing new and innovative sources of finance affect the performance of SEBs. Meanwhile, this effect varies among different aspects of performance. The study concluded that SEBs prefer equity to debts. The performance of SBEs is mainly derived through accessibility to funds, governmental support, using innovative finance and the availability of collateral. Implications This study contributes to the literature and industry by being the first to examine the accessibility of innovative sources of funds for SEBs in Qatar and their impact on different dimensions of performance. Our findings can help decision-makers to consider the impact of diverse sources of funds on different performance dimensions, which affect financing decisions made based on the performance priorities. Moreover, we find a negative impact of governmental support and using crowdfunding on internal business and development performance; this implies that less efficient SEBs, in terms of their internal business and marketing performance, are more active in obtaining both governmental support and crowdfunding, as they may be not eligible for other sources of finance. Our work highlights the key role of adapting to the new accessibility of funds in improving the performance of SBEs in Qatar, which is ultimately reflected in the diversification of the economy. Other Information Published in: Cogent Economics & Finance License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/23322039.2023.2183667